2019
DOI: 10.1002/jsfa.9715
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanofiber (CNF)–sakacin‐A active material: production, characterization and application in storage trials of smoked salmon

Abstract: BACKGROUND Sakacin‐A due to its specific antimicrobial activity may represent a good candidate to develop active packaging solutions for food items supporting Listeria growth. In the present study a protein extract containing the bacteriocin sakacin‐A, produced by Lactobacillus sakei Lb 706 in a low‐cost culture medium containing deproteinized cheese whey, was adsorbed onto cellulose nanofibers (CNFs) to obtain an active material to be used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…As previously explained, pH time course cannot be considered totally representative of sakacin A production due to the possible activation of the ADI pathway with consequent NH 3 production. On the contrary, as lactic acid production is directly linked to bacterial growth, its concentration can be correlated to the presence of sakacin A [27]; concentrations of lactic acid higher than 2 g/L were found when YE concentration was set at its maximum level and above all when in presence of ME, while arginine seems not to be correlated with microbial growth and lactic acid production. Table 3.…”
Section: Optimization Of Sak Medium Formulationmentioning
confidence: 86%
See 4 more Smart Citations
“…As previously explained, pH time course cannot be considered totally representative of sakacin A production due to the possible activation of the ADI pathway with consequent NH 3 production. On the contrary, as lactic acid production is directly linked to bacterial growth, its concentration can be correlated to the presence of sakacin A [27]; concentrations of lactic acid higher than 2 g/L were found when YE concentration was set at its maximum level and above all when in presence of ME, while arginine seems not to be correlated with microbial growth and lactic acid production. Table 3.…”
Section: Optimization Of Sak Medium Formulationmentioning
confidence: 86%
“…Even if slightly higher L. sakei growth (final OD) was obtained in MRS, growth rates were always higher in SAK, highlighting that the formulation containing CWP can effectively support L. sakei growth. The quantification of the antimicrobial activity confirmed that the highest sakacin A production was reached at the end of the exponential phase of each curve [27,35], i.e., at 8 h for cultures inoculated at 5% (v/v) (300 and 333 AU/mL in MRS and SAK respectively) and 16 h for 0.1-0.5% (v/v) (233-267 AU/mL). As expected, the lag phase significantly decreased with the increase of inoculum percentage for both media and, regardless to the inoculum, longer in SAK.…”
Section: Sakei Growth and Sakacin A Production In Mrs And Sak Mediamentioning
confidence: 91%
See 3 more Smart Citations